Genetic diversity and morphological characteristics of native seashore paspalum in Indonesia - Rahayu Rahayu; Fatimah Suwardjo; Ji Bae Eun; Geun Mo Yang; Soo Choi Joon (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rahayu, Fatimah, Bae EJ, Mo YG, Choi JS. 2020. Genetic diversity and morphological characteristics of native seashore paspalum in Indonesia. Biodiversitas 21: 4981-4989. Seashore paspalum (Paspalum vaginatum) is a warm-season turfgrass indigenous to tropical and coastal areas worldwide. The objectives of this study were to measure the genetic diversity and genetic variation of Indonesian seashore paspalum germplasm. Three turf quality, six morphological characters, and ten SSR (microsatellite) markers were used to assess genetic relationships and genetic variation among 22 germplasm resources from Indonesia and one commercial variety (Salam) from United States of America. The results showed significant variation for five morphological characters among 23 tested seashore paspalum accessions. The cluster analysis of morphological characters of 23 seashore paspalum accessions using 0,6 cut off divided into three morphological types: tall high-density, intermediate, and dwarf low-density ecotype. The genetic variation revealed 22 alleles with average number of alleles per locus was 2 and polymorphism information content (PIC) values average was 0.33. The microsatellite marker cluster analysis showed that 23 seashore paspalum accessions were grouped into two major groups, with a genetic similarity coefficient was 0,72. The low level of genetic diversity occurred among Indonesia natural grass germplasm and the genetic distance was relatively low between Indonesian germplasm and Salam variety. The genetic diversity and morphological characteristics will be useful for further study and utilization of Indonesian seashore paspalum germplasm.